Assessment of a dye permeability assay for determination of inactivation rates of Cryptosporidium parvum oocysts. - Jenkins, M B (1997)
The ability to determine inactivation rates of Cryptosporidium parvum oocysts in environmental samples is critical for assessing the public health hazard of this gastrointestinal parasite in watersheds. We compared a dye permeability assay, which tests the differential uptake of the fluorochromes 4'-6-diamidino-2-phenylindole (DAPI) and propidium iodide (PI) by the oocysts (A. T. Campbell, L. J. Robertson, and H. V. Smith, Appl. Environ. Microbiol. 58:3488-3493, 1992), with an in vitro excystation assay, which tests their ability to excyst and, thus, their metabolic potential and potential for infectivity (J.B. Rose, H. Darbin, and C.P. Gerba, Water Sci. Technol. 20:271-276, 1988). Formaldehyde-fixed (killed) oocysts and untreated oocysts were permeabilized with sodium hypochlorite and subjected to both assays. The results of the dye permeability assays were the same, while the excystation assay showed that no excystation occurred in formaldehyde-fixed oocysts. This confirmed that oocyst wall permeability, rather than metabolic activity potential, was the basis of the dye permeability viability assessment. A previously developed protocol (L. J. Anguish and W. C. Ghiorse, Appl. Environ. Microbiol. 63:724-733, 1997) for determining viability of oocysts in soil and sediment was used to examine further the use of oocyst permeability status as an indicator of oocyst viability in fecal material stored at 4 degrees C and in water at various temperatures. Most of the oocysts in fresh calf feces were found to be impermeable to the fluorochromes. They were also capable of excystation, as indicated by the in vitro excystation assay, and were infective, as indicated by a standard mouse infectivity assay. The dye permeability assay further showed that an increase in the intermediate population of oocysts permeable to DAPI but not to PI occurred over time. There was also a steady population of oocysts permeable to both dyes. Further experiments with purified oocysts suspended in distilled water showed that the shift in oocyst populations from impermeable to partially permeable to fully permeable was accelerated at temperatures above 4 degrees C. This sequence of oocyst permeability changes was taken as an indicator of the oocyst inactivation pathway. Using the dye permeability results, inactivation rates of oocysts in two fecal pools stored in the dark at 4 degrees C for 410 and 259 days were estimated to be 0.0040 and 0.0056 oocyst day-1, respectively. The excystation assay gave similar inactivation rates of 0.0046 and 0.0079 oocyst day-1. These results demonstrate the utility of the dye permeability assay as an indicator of potential viability and infectivity of oocysts, especially when combined with improved microscopic methods for detection of oocysts in soil, turbid water, and sediments.